Process of victimization as a socio-psychological phenomenon - Rohatsen, Oleg Y. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The conception of victimization as a process of turning an individual into a victim of unfavorable circumstances of life was considered in the article. The structure of victimization and its levels were disclosed. Features of criminogenic and victimogenic situations were described. The factors of victimization of Belarusians were identified according to the analysis of scientific developments in this direction. The consequences of victimization were also considered in the article.